2000
DOI: 10.1175/1520-0477(2000)081<0797:aiorcf>2.3.co;2
|View full text |Cite
|
Sign up to set email alerts
|

An Intercomparison of Radiation Codes for Retrieving Upper–Tropospheric Humidity in the 6.3–mm Band: A Report from the First GVaP Workshop

Abstract: An intercomparison of radiation codes used in retrieving upper-tropospheric humidity (UTH) from observations in the v2 (6.3 /xm) water vapor absorption band was performed. This intercomparison is one part of a coordinated effort within the Global Energy and Water Cycle Experiment Water Vapor Project to assess our ability to monitor the distribution and variations of upper-tropospheric moisture from spaceborne sensors. A total of 23 different codes, ranging from detailed line-by-line (LBL) models, to coarser-re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 18 publications
2
31
0
Order By: Relevance
“…Studying three-hourly weather data from 15 000 worldwide stations, Dai (2001) found that the most frequent (morning) hour of showery precipitation over water is out of phase with those over land and the latter exhibited large seasonal variability. Similar large variability was also reported in wind measurements (Dai and Deser, 1999) and cloud and water vapor data (Soden, 2000;Tian et al, 2004). However, such strong zonal variations of the diurnal amplitude would require very dense RO soundings to suppress aliasing effects.…”
Section: Discussionsupporting
confidence: 78%
“…Studying three-hourly weather data from 15 000 worldwide stations, Dai (2001) found that the most frequent (morning) hour of showery precipitation over water is out of phase with those over land and the latter exhibited large seasonal variability. Similar large variability was also reported in wind measurements (Dai and Deser, 1999) and cloud and water vapor data (Soden, 2000;Tian et al, 2004). However, such strong zonal variations of the diurnal amplitude would require very dense RO soundings to suppress aliasing effects.…”
Section: Discussionsupporting
confidence: 78%
“…RTTOV uses HITRAN-2000 (Rothman et al, 2003) as spectroscopic data base. For the specific case of the 6.3 µm strong vibration-rotation absorption band by water vapor, the RTTOV model takes into account the water vapor continuum (foreign-broadening and self-broadening, model CKD-2.4; Clough et al, 1989) that has a non-negligible contribution in the water vapor band (e.g., Stephens et al, 1996, andSoden et al, 2000). Based on the work of Brunel and Turner (2003) referenced in the RTTOV v9 user guide, the bias uncertainty of RTTOV with respect to the Meteosat water vapor channel is < 0.1 K, with a standard deviation of > 0.3 K.…”
Section: Methodsmentioning
confidence: 99%
“…A weak point of the UTH algorithm is the fact that retrieval errors of the HIRS/2 channel 12 brightness temperature scale linearly with the relative uncertainty in UTH (Soden et al, 2000). This implies that the largest uncertainties of UTH occur just in the ice supersaturated situations.…”
Section: Influence Of Retrieval Errorsmentioning
confidence: 99%